Conservation in the Soviet Union - Pryde, Philip R. (London Cambridge University Press, 1972)
Comprehensive survey of resource management in the Soviet Union, analyzing attitudes and accomplishments in the field of conservation of natural resources.
Include Index and Bibliography
Keywords: Conservation of natural resources -- Soviet Union -- Natural areas